2013
DOI: 10.1007/978-3-319-01619-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Predicted No-Effect Concentration and Risk Assessment for 17-[Beta]-Estradiol in Waters of China

Abstract: Contamination of the aquatic environment by EDCs has received considerable attention from scientists, government officials, and the public. E2, one of the EDCs with high estrogenic effect, has the potential to cause multiple endocrine-disrupting effects, even at small concentrations. In the present review, the toxicity of E2 to aquatic organisms was reviewed. Results of published studies show that, for aquatic species, reproductive effects were the most sensitive endpoint for E2 exposure.Although the risks pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…Additionally, there are several distributions available to derive the SSD for ERA ( Wang et al, 2015 ), such as log-normal, log-logistic, triangular, or Burr Type III ( Jin et al, 2011 ; Wu et al, 2014 ; Wu et al, 2013 ). The linearized log-normal distribution has become the most adopted approach by most researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there are several distributions available to derive the SSD for ERA ( Wang et al, 2015 ), such as log-normal, log-logistic, triangular, or Burr Type III ( Jin et al, 2011 ; Wu et al, 2014 ; Wu et al, 2013 ). The linearized log-normal distribution has become the most adopted approach by most researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Although their concentrations in environment are at trace levels, environmental estrogens are difficult to be removed. They can be assimilated by humans through food intake and then threaten human health 4 . Sometimes, several estrogen metabolites and estrogens in non-active states discharged into environment can be converted back to the active states, adding the removal difficulty 5 6 .…”
mentioning
confidence: 99%
“…In Caldwell's opinion, for long-term exposures to steroid estrogens in surface water (>60 d), the PNECs were 6, 2, 60, and 0.1 ng/L for E1, E2β, E3, and EE2, respectively, [42]. However, Wu's research [43] showed the more reasonable PNEC value was 0.73 ng E2β/L, which was consistent with other E2β PNEC values derived by the European Union (0.4 ng/L) for protecting aquatic life (European Union 2011). Caldwell's data were derived from a species sensitivity distribution (SSD) curve constructed from 21 in vivo NOECs.…”
Section: Ecological Risk Of Ses In Erhai Lake Basinmentioning
confidence: 90%